Penerapan Pendekatan Healing Environment pada Rumah Perawatan Paliatif bagi Penderita Kanker - Pauline Susanto; Sriti Mayang Sari; filipus priyo suprobo (Intra, 2016)
People that suffer from cancer have a heavy medical burden. The side effect of their healing process is not only drains their energy and money, but also impacts on their mental. The interior design of Palliative Care’s House is designed to stimulate the positive energy around them. Healing Environment approach is used as a reference to create an environment that can reduces stressors from surrounding. It hopes that by being in this house, people can have enough rest and gain much hopes and positive energies. Palliative Care’s concept, which enhances the importance of patient’s psychology, applied by providing a clinic and therapies facilities for cancer patient to make them feel pampered and safe.